Pengembangan Karakter Pada Profil Pelajar Pancasila? - Nugraha, Eric Septian; Jahroni, Ahmad; Hakim, Kaka Luqman (AGUSPATI RESEARCH INSTITUTA, 2024)
The purpose of this study is to find out about the pancasila student profile. The study report USES a descriptive qualitative method by doing note notes because of data generated by listening to oral narratives from youtube channel learn the digital era